Digital Transformation and the Future of Organizational Leadership: Challenging of Knowledge Management - Shvetsova Olga (Business, Management and Economics: Research Progress Vol. 9, 2024)
Ensuring innovative growth and maintaining a competitive advantage is essential across industries, particularly in the fast-evolving automotive sector. As innovation drives development, the automotive industry must prioritize adopting advanced technologies and fostering continuous learning to remain highly competitive. Knowledge management (KM) is crucial in this process, significantly shaping strategic leadership actions within automotive companies. The global automotive industry has achieved notable success through accelerated KM practices and technology transfer initiatives. However, the growth of the Asian automotive sector remains closely tied to the performance of major international corporations, raising questions about its ability to sustain a competitive position independently through its own technological and knowledge capabilities. This study examines the role of KM-enhanced organizational leadership in driving competitiveness within the automotive industry. It seeks to identify key KM-driven factors that impact organizational leadership and assess their influence on market competitiveness. Aims: The study aims to investigate the KM elements that influence organizational leadership development within Asian automotive companies. It examines the relationship between KM practices and leadership effectiveness, using Cronbach’s alpha test to assess reliability. Methods: This research employs quantitative data analysis and considers the automotive industry’s unique characteristics. Using data from publicly available sources, it applies Cronbach’s alpha to test the reliability of KM and leadership variables. Limitations include the reliance on open-source data and a statistical focus on key identified factors. Results: The analysis of two prominent automotive corporations in Asia revealed significant insights into how KM-based leadership influences technology adoption and innovation. The study identified a strong interdependence between KM practices and leadership strategies, underscoring their combined impact on competitiveness. Conclusion: The findings suggest that organizational leadership when effectively integrated with KM practices, can act as a catalyst for technological advancement in automotive companies. Managers can use these insights to develop strategic programs that strengthen KM processes, enhance leadership capabilities, and improve technology transfer within Asian automotive firms.